Behavior management of vocal tics among learners with disabilities through functional analysis - Bermudo, Gina Luna; Bustos, Marie Therese Angeline P.; Ho, Leticia Penano; Muega, Maricris B. Acido; Echavia, Darlene B. (Quezon City College of Education, University of the Philippines Diliman, 2018)
While the nature of tic disorders, including vocal tics (VT), have yet to be determined as either neurobiological or behavioral, multiple studies agreed that prevailing interventions for these disorders remain based on behavioral methods. One such intervention is Functional Analysis (FA), which aims to determine the relationship between the behavior and the individual or their environment, focusing on the presence or absence of the other. This study assessed the effectiveness of FA as an intervention method for managing VT of five learners with varying comorbidities by measuring the effects of FA on the frequency of VT among these learners under the four FA conditions. It also gathered insights from these learners, their parents, and their teachers on the implementation of the FA intervention program. It consisted of a series of 12 one-hour sessions, with the goal of helping the learners acquire the skill in decreasing the occurrence of their VT. While there was improvement among all learners concerning the reduction of VT occurrence during the implementation of the FA program, these learners, their parents, and their teachers expressed reservations on the program, as they believed it to be a novel and an untested intervention approach. Nonetheless, the results recommend that FA could be a useful intervention method for VT, although its sustainability and adaptiveness to real-life scenarios could be improved further. Future research may consider studying other factors of the FA intervention program, including standardizing the definition and measurement of VT frequency and severity.
Thesis
Includes bibliographical references (129-141 leaves).
Keywords: Students with disabilites -- Behavior modification; Behavior disorders in children